2010
DOI: 10.1007/s00210-010-0507-8
|View full text |Cite
|
Sign up to set email alerts
|

Glycyl-glutamine (β-endorphin30-31) inhibits morphine-induced dopamine efflux in the nucleus accumbens

Abstract: Glycyl-glutamine (Gly-Gln) is an endogenous dipeptide that is synthesized from beta-endorphin post-translationally. Previously, we showed that Gly-Gln prevents acquisition of morphine-conditioned place preference, a behavioral test of morphine reward, but does not interfere with morphine analgesia. In this study, we tested the hypothesis that Gly-Gln inhibits morphine reward by blocking morphine-induced dopamine efflux in the nucleus accumbens (NAc). Extracellular dopamine and 3,4-dihydroxyphenylacetic acid (D… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
5
0

Year Published

2011
2011
2018
2018

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 28 publications
0
5
0
Order By: Relevance
“…It apparently acts by a unique and as yet undefined mechanism [5]. Along with inhibition of voluntary alcohol consumption activity, Gly-Gln has also been shown to inhibit the reward benefiting effects of morphine and nicotine [8; 9; 10]. All these findings corroborate the fact that Gly-Gln has an interesting and potentially useful pharmacological activity.…”
mentioning
confidence: 75%
“…It apparently acts by a unique and as yet undefined mechanism [5]. Along with inhibition of voluntary alcohol consumption activity, Gly-Gln has also been shown to inhibit the reward benefiting effects of morphine and nicotine [8; 9; 10]. All these findings corroborate the fact that Gly-Gln has an interesting and potentially useful pharmacological activity.…”
mentioning
confidence: 75%
“…79 More recently it was shown that glycyl-glutamine abolishes the rewarding effect of morphine by inhibition of morphine-induced dopamine release in the nucleus accumbens. 80 The receptor target of glycyl-glutamine remains still unknown, but the inability to antagonize its effects with opioid antagonists precludes an opioid receptor target. 77 Currently no human data are available on the effect of glycyl-glutamine on depressed breathing.…”
Section: Glycyl-l-glutaminementioning
confidence: 99%
“…The tripeptide thyrotropin-releasing hormone (Glu-His-Pro-NH 2 ) is a potent but short-lived respiratory stimulant in animals and humans. [80][81][82][83][84] It induces rhythmic bursting in respiratory neurons of the nucleus tractus solitarius through modulation of membrane excitability. 81 In rabbit and monkey, thyrotropin-releasing hormone produces a rapid arousal from penthobarbital anesthesia.…”
Section: Thyrotropin-releasing Hormonementioning
confidence: 99%
See 1 more Smart Citation
“…Dopamine release decreases, when an expectation ends. Increasing effect of morphine on dopamine release from the nucleus accumbens is suppressed by Gly-Gln, which is one of the degradation products of β-endorphin, and thus rewarding effect of morphine is eliminated [27] [28]. People who intend to manage the perceptions get the population to come along by deliberately shifting the population from one expectation to another.…”
Section: Focusing Attention On a Specific Point Creating An Expectationmentioning
confidence: 99%